Ritual and vulnerability - Brock, Gary (Journal of religion and health, 1990)
Crises are viewed as direct challenges to one's communal patterns of living. The individual response to crisis(-es) is mediated by the "grand rituals of the culture." Ritual behaviors are adaptive behaviors. For the religious community, ritual becomes liturgy. Rite-as-liturgy is a profound statement about the meeting of the human and the divine. Ritual behaviors are understood as liturgical and/or sacramental responses to those crises that bring one to the brink of chaos.